5-Azacytidine prevents relapse and produces long-term complete remissions in leukemia xenografts treated with Moxetumomab pasudotox - Müller, Fabian; Cunningham, Tyler; Stookey, Stephanie; Tai, Chin-Hsien; Burkett, Sandra; Jailwala, Parthav; Stevenson, Maryalice Stetler; Cam, Margaret C.; Wayne, Alan S.; Pastan, Ira (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Moxetumomab pasudotox (Moxe) is a chimeric protein composed of an anti-CD22 Fv fused to a portion of Pseudomonas exotoxin A and kills CD22-expressing leukemia cells. It is very active in hairy-cell leukemia, but many children with relapsed/refractory acute lymphoblastic leukemia (ALL) either respond transiently or are initially resistant. Resistance to Moxe in cultured cells is due to low expression of diphthamide genes (DPH), but only two of six ALL blast samples from resistant patients had low DPH expression. To develop a more clinically relevant model of resistance, we treated NSG mice bearing KOPN-8 or Reh cells with Moxe. More than 99.9% of the cancer cells were killed by Moxe, but relapse occurred from discrete bone marrow sites. The resistant cells would no longer grow in cell culture and showed major chromosomal changes and changes in phenotype with greatly decreased CD22. RNA deep sequencing of resistant KOPN-8 blasts revealed global changes in gene expression, indicating dedifferentiation toward less-mature B cell precursors, and showed an up-regulation of myeloid genes. When Moxe was combined with 5-azacytidine, resistance was prevented and survival increased to over 5 months in the KOPN-8 model and greatly improved in the Reh model. We conclude that Moxe resistance in mice is due to a new mechanism that could not be observed using cultured cells and is prevented by treatment with 5-azacytidine.
EVALuna2:34163